A Multicenter Observational Cohort Study to Evaluate the Effects of Bisphosphonate Exposure on Bone Mineral Density and Other Health Outcomes in Osteogenesis Imperfecta. (7th January 2019) - Bains, Jaskaran S; Carter, Erin M; Citron, Kate P; Boskey, Adele L; Shapiro, Jay R; Steiner, Robert D; Smith, Peter A; Bober, Michael B; Hart, Tracy; Cuthbertson, David; Krischer, Jeff; Byers, Peter H; et al.
Abstract: Osteogenesis imperfecta (OI) is characterized by low bone mass and bone fragility. Using data from a large cohort of individuals with OI from the Osteogenesis Imperfecta Foundation's linked clinical research centers, we examined the association between exposure to bisphosphonate (BPN) treatment (past or present) and lumbar spine (LS) areal bone mineral density (aBMD), fractures, scoliosis, and mobility. From 466 individuals, we obtained 1394 participant‐age LS aBMD data points. Though all OI subtypes were examined, primary analyses were restricted to type I OI (OI‐1). Using linear regression, we constructed expected OI‐1 LS aBMD‐for‐age curves from the data from individuals who had never received BPN. LS aBMD in those who had been exposed to BPN was then compared with the computed expected aBMD. BPN exposure in preadolescent years (age <14 years) was associated with a LS aBMD that was 9% more than the expected computed values in BPN‐naïve individuals ( p  < 0.01); however, such association was not observed across all ages. Exposure to i.v. BPN and treatment duration> 2 years correlated with LS aBMD in preadolescent individuals. BPN exposure also had a significant association with non‐aBMD clinical outcome variables. Logistic regression modeling predicted that with BPN exposure, a 1‐year increase in age would be associated with an 8.2% decrease in fracture probability for preadolescent individuals with OI‐1, compared with no decrease in individuals who had never received any BPN ( p  < 0.05). In preadolescent individuals with OI‐1, a 0.1 g/cm 2 increase in LS aBMD was associated with a 10.6% decrease in scoliosis probability, compared with a 46.8% increase in the BPN‐naïve group ( p  < 0.01). For the same changes in age and LS aBMD in preadolescent individuals, BPN exposure was also associated with higher mobility scores ( p  < 0.01), demonstrating that BPN treatment may be associated with daily function. © 2018 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.